Rancang Bangun Sistem Monitoring Suhu Stroberi Segar dalam Refrigerator Berbasis Internet of Things: Design of Temperature Monitoring System for Fresh Strawberries in a Refrigerator Based on Internet of Things (IoT - Lestari, Hanis Adila; Kurniawan, Anri; Yuwono, Triat Adi (Politeknik Pertanian Bogor, 2024)
Strawberry is highly perishable due to their short shelf life and susceptibility to damage. Strawberries' quality and freshness require storage at an optimal and stable temperature, ideally between 0–4 °C. If the temperature is too low or too high, it may experience a decline in quality, nutritional value, and physical damage such as wilting, decay, or excessive moisture. This study aims to develop an automatic temperature monitoring system enabling users to monitor storage conditions via a web-based application. The system utilizes a DHT22 temperature and humidity sensor, ESP32 microcontroller, and an I2C LCD connected to Thingspeak.com to monitor temperature over 12 days at 4°C, calibrated using a thermohygrometer. The results show fruit color tends to darken during storage, with decreasing a* (redness) and b* (yellowness) values. The pH of the strawberries ranges from 3 to 6, indicating low acidity and falling below the ideal range. Weight loss percentage increased during storage, especially in cut strawberries with non-vacuum packaging, reaching 74,52%. Additionally, the moisture content in both whole and cut strawberries stored in non-vacuum packaging increased during storage. At 4 °C, the quality of strawberries could not be maintained for 20 days based on parameters such as color, pH, weight loss, and moisture content.